DIFFERENCES BETWEEN CADET AND YOUNGER CADET HANDBALL PLAYERS IN SPECIFIC MOTOR ABILITIES - Dinko Vuleta; Dragan Milanović; Andrija Nikolić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The differences were analyzed between 12 cadet and 12 younger cadet handball players in indicators of specific motor abilities. Central and dispersive parameters were computed of the variables obtained in the testing procedures. The acceptable significance level was set at p≤.05. The results of MANOVA showed significant statistical differences (Wilks´ Lambda=.459; p<.01) between the two analyzed groups of handball players. The results of t-test for independent samples of variables assessing specific agility and specific power of arms confirmed statistically significant differences between the groups in all the variables: quickness between goal posts and 4 m line 4 m (KIWI), sitting handball throw (RADAR4), 6-m-line basic stance handball throw (RADAR6), 9-m-line basic ground shot after the three-step approach (RADAROU) and 9-m-line jump shot from dribbling (RADAR-SŠ). The obtained results are in accordance with the biological factors of maturation and with the selective approach to the training program design and implementation of training programmes aimed at the development of explosive power of the throwing type in younger age categories of handball players.